Exploring the Resilience of School Principals: Demographic Determinants and Institutional Influences in a Developing Region - St Nurjaningsih; Gunarhadi Gunarhadi; Sunardi Sunardi; Sukarmin Sukarmin (Ianna Journal of Interdisciplinary Studies)
Background: School principals are often challenged in exercising their authority, especially during educational policy adjustments. Resilience is one factor that can overcome these problems. However, the exploration of resilience, especially among school principals, is still limited, especially in terms of demographic factors such as age, work experience, and education level.